Legal principles in banking and structured finance - Hughes, Martin (Haywards Heath, West Sussex : Tottel Pub., 2006)
This book covers a wide range of crucial areas, including: Core concepts in bank lending; bills of exchange and promissory notes; bond issues -- a banking lawyer's unique perspective; syndicated lending; recent case law on lenders' powers; the financial collateral regulations; the contracts (right of third parties) act; trusts and trustees in secured and stuctured finance; legal drafting
Rev. ed. of: Selected legal issues for finance lawyers. London : LexisNexis, c2003.
Includes index.
gau 18/06/14
Loans
Keywords: Finance -- Law and legislation -- England; International finance -- Law and legislation -- England